2018
DOI: 10.1038/s41598-018-20064-2
|View full text |Cite
|
Sign up to set email alerts
|

Preferential amplification of a human mitochondrial DNA deletion in vitro and in vivo

Abstract: We generated induced pluripotent stem cells (iPSCs) from patient fibroblasts to yield cell lines containing varying degrees of heteroplasmy for a m.13514 A > G mtDNA point mutation (2 lines) and for a ~6 kb single, large scale mtDNA deletion (3 lines). Long term culture of the iPSCs containing a single, large-scale mtDNA deletion showed consistent increase in mtDNA deletion levels with time. Higher levels of mtDNA heteroplasmy correlated with increased respiratory deficiency. To determine what changes occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…This 'clonal expansion' of the deletionbearing mtDNA molecules (DmtDNA) in affected individuals can hardly be explained by the sporadic character of the pathogenesis. In fact, a recent comparative study of the expansion of various aberrant mtDNA molecules in dividing induced pluripotent stem cells demonstrated that DmtDNA are preferentially replicated compared to controls or those bearing point mutations (Russell et al, 2018). This finding is in line with other analyses implying that point mutation-bearing mtDNA molecules do not exhibit advantageous replication and clonal expansion (Pallotti et al, 1996;Wilson et al, 2016), and supports the idea of preferential expansion of DmtDNA (Picard et al, 2016).…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…This 'clonal expansion' of the deletionbearing mtDNA molecules (DmtDNA) in affected individuals can hardly be explained by the sporadic character of the pathogenesis. In fact, a recent comparative study of the expansion of various aberrant mtDNA molecules in dividing induced pluripotent stem cells demonstrated that DmtDNA are preferentially replicated compared to controls or those bearing point mutations (Russell et al, 2018). This finding is in line with other analyses implying that point mutation-bearing mtDNA molecules do not exhibit advantageous replication and clonal expansion (Pallotti et al, 1996;Wilson et al, 2016), and supports the idea of preferential expansion of DmtDNA (Picard et al, 2016).…”
Section: Introductionsupporting
confidence: 66%
“…In contrast to point mutations, pathogenic mtDNA deletions typically arise de novo and, with rare exceptions (Chinnery et al, 2004), are not inherited by the offspring (Ng and Turnbull, 2016;Kauppila et al, 2017). Phenotypically, primary deletions manifest as the often-fatal Pearson syndrome in infancy, Kearns-Sayre syndrome (KSS) in childhood and adolescence, or late onset progressive external ophthalmoplegia (PEO) (Rocha et al, 2018;Russell et al, 2018). In the clinical scope, the mtDNA mutation load found in sporadic KSS, PEO and Pearson's syndrome is extremely high (>80% in affected tissues) (Moraes et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Even though this adaptation could seem beneficial, it might be detrimental if the proportion of damaged molecules is not reduced. Indeed, deleted mtDNA can accumulate by virtue of a replicative advantage over wild type molecules [35]. In our experimental model, the administration of enalapril was associated with lower abundance of mtDNA 4834 deletion ( Figure 3B) and reduced severity of oxidative lesions to functional regions of mtDNA (Cytb and D-Loop) (Figure 4).…”
Section: Discussionmentioning
confidence: 72%
“…It was initially proposed that deletions, being smaller, replicate in a shorter time, leading to a replicative advantage [19,29]. This was observed in some specific cases, namely for fast-proliferating cells [30] and cells recovering their mtDNA populations after heavy depletion [31]. However, through numerical simulations it has been shown that the size-induced advantage cannot explain the observed accumulation in non-replicating muscle fibres, especially in short-lived animals [24].…”
Section: Introductionmentioning
confidence: 99%